AB0395 Restart for Sustaining Remission of Rheumatoid Arthritis in Use of Etanercept: Resume Study. (10th June 2014) - Inui, K.; Koike, T.; Tada, M.; Sugioka, Y.; Mamoto, K.; Okano, T.; Sakawa, A.; Fukushima, K.; Nakamura, H.
Abstract : Background: Biological agents have recently proven to be an effective treatment for rheumatoid arthritis (RA). Biological agents are particularly recommended for patients with active RA who may incur further joint damage. However, in daily clinical practice, some patients with RA reject treatment with biological agents because of the high cost. To save costs for patients the use biological agents may be limited to only when disease activity is high. However, after biological agents have significantly reduced disease activity, and the biological agents are discontinued, potential flare-ups of disease activity are of concern. Objectives: To examine if we could reduce the use of biologic agents, we tested the efficacy of restarting the same biologic agents in RA patients only when disease activity flared up. We conducted a prospective non-randomized non-blinded study using etanercept to control disease activity and prevent further joint destruction in patients with RA. Methods: BIO-naive RA patients (N=31) with moderate to severe disease activity (DAS28≥3.2) were enrolled with written consent during 1 January 2011–31 December 2012. The average age was 60 years, and average disease duration was 5 years. Etanercept (50 mg/week) was administered each week until disease activity was measured as low (DAS28-ESR<3.2). Patients were then observed every 2 months. If disease activity recurred, the same dose of etanercept was re-administered weekly and patients were observed every 2 months. This strategy was maintained for 2 years. We aimed to control the disease activity below the low level (DAS28-ESR<3.2). If patients could not reach low disease activity after the administration of etanercept within 3 months, we used combined medicines with other synthetic disease-modifying antirheumatic drugs except glucocorticoid and tacrolimus. If low disease activity could not be achieved within 6 months, patients were withdrawn from the trial. Results: Of the 31 patients enrolled in this study, 13 were withdrawn because of an inadequate response to etanercept, and 5 had no flare-up of disease activity after discontinuation of etanercept. In the remaining 13 cases (8 women) the strategy of re-administering etanercept when disease activity was above the low level was maintained. The mean dose of methotrexate was 10 mg/w, rheumatoid factor was positive in 11 patients, and the mean follow-up period was 20.5 months. All 13 cases of etanercept re-administration during a flare-up after discontinuation achieved low disease activity in 3.7 months on average. Cost saving calculations included 5 patients who maintained low disease activity without restarting etanercept, and were calculated as if etanercept treatment was continued. The actual saving was found to be approximately 35%. Conclusions: All patients for whom etanercept was re-administered when a flare-up occurred after discontinuation of etanercept had achieved low DA at final follow up. Joint damage has yet to be evaluated. However, low DA was achieved at a low cost to the state. Disclosure of Interest: K. Inui Grant/research support: Chugai Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., Astellas Pharma Inc., Abbvie GK, Eisai Co., Ltd., MSD K.K., Speakers bureau: Bristol-Myers K.K., Takeda Pharmaceutical Corporation, Ltd., Chugai Pharmaceutical Co., Ltd., Janssen Pharmaceutical K.K., Abbvie GK, Astellas Pharma Inc., T. Koike Grant/research support: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, Speakers bureau: Takeda Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Chugai Pharmaceutical, Eisai, Abbott Japan, Teijin Pharma, Banyu Pharmaceutical and Ono Pharmaceutical, M. Tada: None declared, Y. Sugioka: None declared, K. Mamoto: None declared, T. Okano: None declared, A. Sakawa: None declared, K. Fukushima: None declared, H. Nakamura Grant/research support: Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Nippon Zoki Pharmaceutical Co., Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Takeda Pharmaceutical Co., Ltd., Hisamitsu Pharmaceutical Co., Inc., Ono Pharmaceutical Co., Ltd., Osteopharma Inc., Teijin Pharma Ltd., Asahi Kasei Pharma Co., Speakers bureau: Eisai Co., Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Ono Pharmaceutical Co., Ltd., Taisho Toyama Pharmaceutical Co., Ltd., Eli Lilly Japan K.K., Asahi Kasei Pharma Co., Teijin Pharma Ltd., Astellas Pharma Inc., Pfizer Japan Inc., Nippon Zoki Pharmaceutical Co., Ltd., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K. DOI: 10.1136/annrheumdis-2014-eular.1098